DC-electro softening in soda lime silicate glass: An electro-thermal analysis. (1st July 2018) - Pinter, Lorenzo; Biesuz, Mattia; Sglavo, Vincenzo M.; Saunders, Theo; Binner, Jon; Reece, Mike; Grasso, Salvatore
Abstract: DC-electric field-induced softening was investigated in soda lime glass. The application of a DC current causes a migration of Na ions towards the cathode resulting in the formation of a sodium depleted layer close to the anode where a localized voltage drop ignites electrical arcs through the glass. This effect is strongly asymmetric with respect to the applied DC polarity and, at the anode, it induces strong photoemission (optical transition of alkali elements) sharp rise in temperature and increased electrical resistance. It appears that electrolytic effects and sodium migration play a fundamental role as triggering mechanisms of DC-electric field-induced softening. Graphical abstract: Unlabelled Image